Microinteractions - Saffer, Dan (O'Reilly, 2013)
It's the little things that turn a good digital product into a great one. With this practical book, you'll learn how to design effective microinteractions: the small details that exist inside and around features. How can users change a setting? How do they turn on mute, or know they have a new email message? Through vivid, real-world examples from today's devices and applications, author Dan Saffer walks you through a microinteraction's essential parts, then shows you how to use them in a mobile app, a web widget, and an appliance. You'll quickly discover how microinteractions can change a product from one that's tolerated into one that's treasured. Explore a microinteraction's structure: triggers, rules, feedback, modes, and loops Learn the types of triggers that initiate a microinteraction Create simple rules that define how your microinteraction can be used Help users understand the rules with feedback, using graphics, sounds, and vibrations Use modes to let users set preferences or modify a microinteraction Extend a microinteraction's life with loops, such as “Get data every 30 seconds”